MENGATASI KESULITAN DALAM MENGAMBIL KEPUTUSAN KARIR MENGGUNAKAN PENDEKATAN TRAIT AND FACTOR - Manasikana, Arina; Kiswantoro, Arista; Sumarwiyah, Sumarwiyah (Universitas Muria Kudus, 2024)
The purpose of the research conducted was to find factors that cause students to experience difficulties in career decision making and help overcome difficulties in career decision making. This research uses a trait and factor approach. This type of research is qualitative case study. The research subjects were students of class XI electronics and XII graphical production at SMK N 1 Kalinyamatan. The data collection techniques used are observation, interview, and documentation techniques. The data analysis used is flow data analysis or flow (flow model analysis). The results of the study prove that the application of the Trait and Factor approach with the problem of difficulty in making student career decisions is effective in dealing with these problems. The problems of counselee I and counselee II have the same causal factors, which are differences of opinion with parents and the family economy and not knowing their talents and interests and not knowing about the world of work. The implementation of the trait and factor approach to the problem can be handled well, the counselee can make career decisions about his future and understand the consequences of the choices he makes.